Hymenasplenium perriei (Aspleniaceae), a new fern species from Fiji - Xu, Ke-Wang; Zhou, Xin-Mao; Liao, Wen-Bo; Zhang, Li-Bing (Phytotaxa, 2018)
A new fern species, Hymenasplenium perriei (Aspleniaceae), from very shaded and wet rocks in southeastern Fiji, is described and illustrated based on our morphological and recent phylogenetic studies. The new species is distinguished by its phyllopodia 2–3(–10) mm apart, marginal teeth irregular and usually with notches, veins usually terminating in marginal teeth below the notch or sometimes in the teeth, and sori inframedial.